The first international conference on SYNGAP1-related brain disorders: a stakeholder meeting of families, researchers, clinicians, and regulators - Monica Weldon; Murat Kilinc; J. Lloyd Holder; Gavin Rumbaugh (Journal of Neurodevelopmental Disorders, 2018)
Abstract Background Pathologic mutations in SYNGAP1 cause a genetically defined form of intellectual disability (ID) with comorbid epilepsy and autistic features. While only recently discovered, pathogenicity of this gene is a relatively frequent genetic cause of classically undefined developmental delay that progresses to ID with commonly occurring comorbidities. Main body A meeting of 150 people was held that included affected individuals and their caregivers, clinicians that treat this and related brain disorders, neuroscientists that study SYNGAP1 biology or the function of related genes, and representatives from government agencies that fund science and approve new medical treatments. The meeting focused on developing a consensus among all stakeholders as to how best to achieve a more fundamental and profound understanding of SYNGAP1 biology and its role in human disease. Short conclusion From all of these proceedings, several areas of consensus emerged. The clinicians and geneticists agreed that the prevalence of epilepsy and sensory processing impairments in SYNGAP1-related brain disorders approached 100%. The neurobiologists agreed that more basic research is needed to better understand the molecular and cellular functions of the Syngap1 gene, which will lead to targets for therapeutic intervention. Finally, everyone agreed that there is a pressing need to form a robust patient registry as an initial step toward a prospective natural history study of patients with pathogenic SYNGAP1 variants.